L'informatique juridique au Québec : état de la question - Le May, Denis (Les Cahiers de droit, 1978)
The purpose of the present paper is to evaluate current Quebec and some Canadian computerized legal information projects. The most important part of the paper studies projects undertaken in relation with either one of the main sources of the law in Quebec: first, statutes and regulations, second, case law and, finally, legal writings (books and periodicals). A very brief survey enumerates the main problems created by the impact of the computer and the legal challenge that it represents (crime by computer, EFT, etc.). Future perspectives are outlined, taking into consideration, in part, what is done in certain other countries. The situation is described as it was during and up to the first six months of 1978.